A fertility-oriented method for histological processing of testicular biopsies in men with azoospermia. (4th July 2021) - Reis, Augusto B.; Reis, Fernando M.; Salles, Paulo G.; Almeida, Fernanda R.C.L.; Martello, Reginaldo; Assis, Wiviane A.; Caldeira-Brant, Andre L.; Tatsuo, Edson S.; Chiarini-Garcia, Hélio
ABSTRACT: The present study was designed to evaluate whether tissue preparation by glutaraldehyde and glycol methacrylate (G/GMA) improves the diagnostic assessment of testicular biopsies from azoospermic men when compared to the standard tissue preparation using Bouin's solution and paraffin. We prospectively included a total of 21 testicular biopsies of sexually mature men aged 29–50 years with infertility and azoospermia. One testicular biopsy fragment from each patient was processed by the G/GMA method, whereas another tissue fragment was contemporarily processed by the conventional Bouin/paraffin (B/P) method. The G/GMA method provided better resolution of cytological details of the seminiferous epithelium, changing the final diagnosis in four cases. The medians of Bergmann's spermatogenesis scores were 0.25 (interquartile range 0.04–0.88) for B/P preparations and 0.79 (interquartile range 0.17–0.96) for G/GMA preparations. Both techniques allowed accurate prediction of sperm recovery from the biopsies (B/P, area under the receiver operating characteristics [ROC] curve 0.88, 95% confidence interval [CI] 0.75–1.00; G/GMA, area under the ROC curve 0.94, 95% CI 0.86–1.00). We conclude that human testicular biopsy preparation with G/GMA improved image resolution under light microscopy and produced more reliable results for the evaluation of spermatogenesis in comparison with B/P, allowing a more precise fertility-oriented diagnosis in azoospermic men. Abbreviations : B/P: Bouin/paraffin; GMA: glycol methacrylate; G/GMA: glutaraldehyde and glycol methacrylate; ICSI: intracytoplasmic sperm injection; OA: obstructive azoospermia; NOA: nonobstructive azoospermia; TESE: testicular sperm extraction.